2011
DOI: 10.3177/jnsv.57.118
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Antioxidant and Anti-Inflammatory Activities of Protocatechualdehyde Isolated from Phellinus gilvus

Abstract: Summary Although various biological activities of Phellinus gilvus (PG) have been reported, the active compounds responsible for these effects are not known. Here, we evaluated the activity of various solvent extracts of PG, and found the ethyl acetate extract (Fd) to be the most active fraction, showing a strong DPPH free radical scavenging activity, and inhibitory effects on LPS-induced nitric oxide (NO) production and COX-2 mRNA expression in RAW264.7 macrophages. Six major compounds were identified from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 21 publications
2
42
0
Order By: Relevance
“…For example, 3,4-DHBA inhibits the abnormal migration and proliferation of vascular smooth muscle cells induced by the ROS generated by platelet-derived growth factor [19]. In addition, it has been reported that 3,4-DHBA has anti-inflammatory activities [3], neuroprotective effects against oxidative stress [10] and anti-cancer activities [13]. …”
Section: Discussionmentioning
confidence: 99%
“…For example, 3,4-DHBA inhibits the abnormal migration and proliferation of vascular smooth muscle cells induced by the ROS generated by platelet-derived growth factor [19]. In addition, it has been reported that 3,4-DHBA has anti-inflammatory activities [3], neuroprotective effects against oxidative stress [10] and anti-cancer activities [13]. …”
Section: Discussionmentioning
confidence: 99%
“…Steroids in general have been reported to play several biological functions such as anti-tumor, anti-oxidant, immune function as well as prevention of common diseases (Phillips et al, 2011). Antrodia camphorata is a medicinal mushroom with reported anti-inflammatory activity (Hseu et al, 2005;Liu et al, 2007;Hsieh et al, 2010;Hseu, Huang, & Hsiang, 2010;Lee et al, 2011b;Liao, Kuo, Liang, Shen, & Wu, 2012;Deng et al, 2013;Chen et al, 2013).…”
Section: Steroidsmentioning
confidence: 99%
“…Meanwhile, it has been reported that PAL can potentially confer anti-fibrosis effects through the inhibition of hepatic stellate cell (HSC) proliferation and levels of transforming growth factor-β1, connective tissue growth factor, type I collagen and type III collagen in tumor necrosis factor-α stimulated HSCs [12]. It has also been reported that PAL possesses other biological activities, including anti-sepsis [13], inhibition of hepatitis B virus replication [14], and anti-inflammatory and antioxidant activities [15]. …”
Section: Introductionmentioning
confidence: 99%